2001
DOI: 10.1258/1357633011936543
|View full text |Cite
|
Sign up to set email alerts
|

The effect of education on patients' willingness to participate in a telemedicine study

Abstract: We assessed the effect of previous education on patients' willingness to participate in a clinical study of telemedicine for hypertensive patients. The design was a cross-sectional study of adult patients arriving for appointments in a hypertension clinic. Of the 259 patients approached, 86% completed a baseline survey and were subsequently asked if they would be willing to participate in a one-year telemedicine study. One hundred and fifty patients (58%) agreed to participate. A stepwise logistic regression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…Many population studies report that a respondents level of education strongly predicts their likelihood of involvement [60,61]. This notion received support in the present study with a higher proportion of participants with some post-school qualification as compared to the general population.…”
Section: Discussionsupporting
confidence: 80%
“…Many population studies report that a respondents level of education strongly predicts their likelihood of involvement [60,61]. This notion received support in the present study with a higher proportion of participants with some post-school qualification as compared to the general population.…”
Section: Discussionsupporting
confidence: 80%
“…However, studies investigating potential benefits of TH have reported some difficulty in recruitment prior to any experience with TH services, with refusals as substantial as 80 per cent (Mair et al, 2006). In addition to socio-demographic factors such as lower academic attainment (Krousel-Wood et al, 2001), older age, poorer health status and rural locality (Mair et al, 2006;Palmas et al, 2006;Van Beijsterveldt et al, 2002;Radler and Ryff, 2010), reasons given for refusal include beliefs that the technology would not be of benefit, or would add nothing to the care they already receive (Subramanian et al, 2004). A qualitative study within the Whole System Demonstrator (WSD) programme, reported three key reservations expressed by patients and carers for non-participation: interventions could undermine self-care, independence and sense of identity; concerns about technical competence to use equipment; and expectations that interventions would disrupt existing services (Sanders et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…1-3 A few studies have addressed patients' willingness to use telemedicine services using standard survey questions. 4,5 Qureshi and Kvedar previously reported that more than 50% of dermatology patients coming to tertiary care hospital practices are amenable to interacting with their dermatologist online and agreeable to having digital skin images sent online. 6,7 In this study, we used a willingness-to-pay (WTP) approach to evaluate patient preferences for telemedicine versus in-person visits.…”
Section: Introduction P Atient Attitudes Toward Telemedicine Havementioning
confidence: 99%